Formação de professores de língua inglesa, reformulações curriculares e resoluções governamentais: um estudo meta analítico - Donadio, Luis Felipe Pereira dos Santos (2015)
The English Language teacher education has undergone profound changes in recent years. A determining factor for these changes was the creation of the National Curricular Guidelines (DCN) by the National Council of Education of the Ministry of Education in order to underpin the development of the curricula of these courses. This research focuses on the analysis of the consequences in the implementation of the DCN for degree courses in language and literature, specifically English language teachers education courses in the process of reformulating their curricula in order to have them aligned to the determinations in the governmental document. For the verification of these consequences articles, dissertations and theses from 2003 (one year after the publication of DCN) to 2014 were analyzed. The chosen research methodology was the qualitative meta-analysis, which allows, with the use of systematic review, to objectively select the works to be analyzed in order to find answers to the research questions. Initially 163 works were selected and, after the systematic review, 12 of these remained for the final analysis. The analysis of these studies indicates that the English language teachers education scenario presents many challenges in the relationship between the proposals of the State and its practical application in the formulation and administration of the curriculum of English language teacher education courses.